2019
DOI: 10.1111/ppl.13040
|View full text |Cite
|
Sign up to set email alerts
|

Rising atmospheric CO2concentration inhibits nitrate assimilation in shoots but enhances it in roots of C3plants

Abstract: We have proposed that rising atmospheric CO 2 concentrations inhibit malate production in chloroplasts and thus impede assimilation of nitrate into protein in shoots of C 3 plants, a phenomenon that will strongly influence primary productivity and food security under the environmental conditions anticipated during the next few decades. Although hundreds of studies support this proposal, several publications in 2018 and 2019 purport to present counterevidence. The following study evaluates these publications as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 67 publications
3
32
0
Order By: Relevance
“…These studies indicated that a wide range of C 3 species, including wheat, show increased growth under CO 2 enrichment, especially if they receive high applications of N (a selected eight references were given for this point that included meta‐analyses and reviews). Continuing, Bloom et al () stated that the four studies we highlighted actually support their conclusions: this is not the case. These studies indicated that for wheat (Hocking and Meyer ), tobacco ( Nicotiana tabacum ; Geiger et al ; Matt et al ) and cucumber ( Cucumis sativus ; Dong et al ) supplied NO 3 − as the sole N source under controlled environment or glasshouse conditions, greatest growth and reduced N accumulation across treatments occurred under elevated CO 2 with high NO 3 − supply.…”
Section: Response To Bloom Et Almentioning
confidence: 67%
See 4 more Smart Citations
“…These studies indicated that a wide range of C 3 species, including wheat, show increased growth under CO 2 enrichment, especially if they receive high applications of N (a selected eight references were given for this point that included meta‐analyses and reviews). Continuing, Bloom et al () stated that the four studies we highlighted actually support their conclusions: this is not the case. These studies indicated that for wheat (Hocking and Meyer ), tobacco ( Nicotiana tabacum ; Geiger et al ; Matt et al ) and cucumber ( Cucumis sativus ; Dong et al ) supplied NO 3 − as the sole N source under controlled environment or glasshouse conditions, greatest growth and reduced N accumulation across treatments occurred under elevated CO 2 with high NO 3 − supply.…”
Section: Response To Bloom Et Almentioning
confidence: 67%
“…Bloom et al () listed several points in our paper (Andrews et al ) where in their view we made false claims in relation to the literature or misinterpreted it. For example, the first point raised was that our statement ‘the weight of evidence in the literature indicates that elevated atmospheric [CO 2 ] does not inhibit NO 3 ‐ assimilation and growth of C 3 vascular plants’ consists of four studies that exposed plants to a specific nitrogen form.…”
Section: Response To Bloom Et Almentioning
confidence: 76%
See 3 more Smart Citations

Serine Metabolic Networks in Plants

Rosa-Téllez,
Casatejada-Anchel,
Alcántara-Enguídanos
et al. 2023
Progress in Botany